2020
DOI: 10.1016/j.arthro.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Is It Time to Abandon the Latissimus Dorsi Tendon Transfer as a Salvage Procedure for Patients With Large Irreparable Rotator Cuff Tears That Failed Primary Repair?

Abstract: The management of large irreparable rotator cuff tears in the young and active patient population without arthritis presents a challenge for shoulder surgeons due to the limited number of treatment options available that provide predictable outcomes. Latissimus dorsi tendon transfer (LDTT) for the treatment of large, irreparable posterosuperior rotator cuff tears or as a salvage procedure for failed surgical (arthroscopic or open) repair was originally introduced in 1988. Multiple studies have reported both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the LDTT group, 59% of patients had a workers' compensation claim and all patients had 1 prior rotator cuff repair, both of which are known risk factors for inferior outcomes. 16,24,39 Additionally, the mean follow-up was 7.0 years in the present study, potentially allowing for outcome deterioration as demonstrated by Gerber et al 12 in their 10-year LDTT outcome study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the LDTT group, 59% of patients had a workers' compensation claim and all patients had 1 prior rotator cuff repair, both of which are known risk factors for inferior outcomes. 16,24,39 Additionally, the mean follow-up was 7.0 years in the present study, potentially allowing for outcome deterioration as demonstrated by Gerber et al 12 in their 10-year LDTT outcome study.…”
Section: Discussionmentioning
confidence: 68%
“…Despite these promising results, unsatisfactory outcomes have been demonstrated when LDTT is performed in the revision setting. 24,30 In a retrospective analysis of 22 patients undergoing LDTT in the setting of prior failed rotator cuff repair, Muench et al 30 reported a postoperative ASES score of 55.8 and a clinical failure rate of 41% at a mean follow-up of 3.4 years. Importantly, all LDTT procedures in our series were performed in the revision setting and 59% were workers’ compensation cases.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Among the various joint preservation surgical approaches described for MIRCTs, 4 , 6 many studies have demonstrated the clinical reliability of LDTT, 4 particularly as a primary procedure. 11 , 12 In a long-term follow-up cohort of 108 patients, the rate of clinical failure of LDTT was 10%, and the conversion to RSA was 4%. Pain relief and improved shoulder function were consistent after 9 years, particularly in younger patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, we should not abandon tendon transfers as a primary procedure for young and active patients with large irreparable rotator cuff tears and intact or repairable subscapularis in the absence of severe osteoarthritis. 22 In the current literature, there is plenty of clinical evidence demonstrating high satisfaction rates in this challenging patient cohort. In contrast, when facing patients with multiple previously failed arthroscopic or open rotator cuff repairs or limited preoperative range of motion, high failure rates and unreliable clinical results may be observed.…”
Section: How the Biomechanical Complexity Of Tendon Transfers In Shoulder Surgery Is Still Robbing Us Of Sleep In 2021mentioning
confidence: 99%